New Eurytomidae species chiefly parasites of legumes seed-eating beetles in Ivory Coast (Lamto) (Hymenoptera Chalcidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Six species of Eurytoma Illiger and one Risbecoma Subba Rao are newly described. E caryedocida n. sp., E. conapionis n. sp., E. lamtoensis n. sp., E. mimosarum n. sp., E. piezotracheli n.sp. et E risbecomaphaga n. sp. are ectoparasites on larvae or pupae of seed-eating beetles (Bruchidae, Apionidae, Cerambycidae, Anthribidae) or seed-eating wasps (Eurytomidae). R. pigrae n. sp. is a seed-eating species attacking one species of Mimosa (Mimosoideae ). A key of the Eurytomidae associated with seed-eating beetles or phytophagous on seed of legumes in West Africa is given.
Keywords: Eurytomidae; new species; legumes; West Africa